Infectious Syphilis in Non-Hispanic Blacks and Hispanics in an Urban STD Clinic - Tai Hunte; Maria L. Alcaide; Ricardo Franco; Khaled Deeb; Jose G. Castro (University of North Florida, 2012)
Syphilis is a complex infectious disease caused by Treponema pallidum and acquired through sexual contact or vertical trans- mission. The natural history of syphilis is divided in primary, secondary, latent and tertiary stages. The syphilis epidemic has evolved over the years. National rates of syphilis infection dropped to the lowest in 2000 and have since increased in certain populations. Men who have sex with men (MSM) account for 60% ofnew infections and high rates occur in individuals with human immune deficiency virus co-infection. This study describes and compares the demographic characteristics, risk factors, and clinical presentation ofinfectious syphilis cases diagnosed in the Miami-Dade Health Department STD clinic among the two main ethnicities (non-Hispanic Black and Hispanic).